Procedural law governing event of default of Islamic financing in Malaysia: issues and challenges - Mat Ali, Syuhaeda Aeni; Hassan, Rusni; Othman, Ahmad Azam (2018)
The state of the economy in Malaysia becomes the worrying issue nowadays. From January to September 2015 more than 20,000 employees lost their jobs and the retrenchment trend continues in 2017. This unemployment situation gravely affects a person’s source of income particularly when he is the sole breadwinner of the family. This unemployment issue further leads to his inability to pay his monthly commitments such as home, personal and car financing. Notwithstanding the above situation, Shariah encourages leniency on the part of the creditor i.e. when the debtor is in a difficulty, to grant him time until it is easy for him to pay. Nonetheless, in Malaysia, the inability to pay debt or non-performing loan/financing entitles the financial institutions (both conventional banks and Islamic financial institutions) to proceed with legal proceeding in civil court. Despite its status as Islamic financing,it is trite that Islamic financing in Malaysia are governed by Shariah principles, legislations which are conventional in nature and to be enforceable in civil court of law. This paper examines procedural laws governing the event of default of Islamic Financing in Malaysia. The methodology adopted in this paper is statutory analysis whereby the relevant legislation namely Rules of Court 2012, Insolvency Act 1967, Limitation Act 1953, Evidence Act 1950, Court of Judicature Act 1964 and the National Land Code 1965 are analysed. The analysis reveals that whilst some of the provisions are sufficient to regulate the event of default of Islamic financing, the present legislation are still inadequate to regulate the same. Hence, the paper also finds significant number of legal issues and challenges derived from the implementation of the laws which require legal reform.